2017
DOI: 10.1097/sla.0000000000002445
|View full text |Cite
|
Sign up to set email alerts
|

Defining Benchmarks for Transthoracic Esophagectomy

Abstract: This outcome analysis of patients with low comorbidity undergoing ttMIE may serve as a reference to evaluate surgical performance in major esophageal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(55 citation statements)
references
References 26 publications
3
51
0
1
Order By: Relevance
“…As shown in Figure 6 , no statistically significant difference existed between the 2 groups (OR =1.76, 95% CI =0.92–3.36, P =0.08), with statistical homogeneity ( I 2 =0%). Additionally, 3 studies containing 499 cases reported 90-day mortality, 21 , 27 , 28 and no statistically significant difference was found between the 2 groups (OR =2.22, 95% CI =0.71–6.98, P =0.17), as shown in Figure 7 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure 6 , no statistically significant difference existed between the 2 groups (OR =1.76, 95% CI =0.92–3.36, P =0.08), with statistical homogeneity ( I 2 =0%). Additionally, 3 studies containing 499 cases reported 90-day mortality, 21 , 27 , 28 and no statistically significant difference was found between the 2 groups (OR =2.22, 95% CI =0.71–6.98, P =0.17), as shown in Figure 7 .…”
Section: Resultsmentioning
confidence: 93%
“…Despite the higher complications caused by MIME, a similar 30-day/in-hospital mortality was observed in the 2 groups, which is in concordance with the 2 latest studies. 27 , 32 This may partly be explained by our previous result that the 2 procedures had similar incidence of causing severe anastomotic leakage. Walters et al 35 suggested that 90-day mortality may provide a better understanding on true death risk for the surgery and patient.…”
Section: Discussionmentioning
confidence: 93%
“…After successful implementation of ERAS programs in colorectal cancer patients, ERAS has been widely implemented in different types of major abdominal surgery with comparable beneficial results (6,(16)(17)(18)(19)(20). The described gains in short-term outcomes include similar or decreased complication and mortality rates, reduction in length of hospital stay, less intensive care unit (ICU) (re)admission, similar or decreased hospital readmission and reduction of hospital costs (16)(17)(18)(19).…”
Section: Improvement In Perioperative Carementioning
confidence: 99%
“…The described gains in short-term outcomes include similar or decreased complication and mortality rates, reduction in length of hospital stay, less intensive care unit (ICU) (re)admission, similar or decreased hospital readmission and reduction of hospital costs (16)(17)(18)(19). Also in patients undergoing an esophagectomy, introduction of an ERAS program resulted in a reduction of overall complications, reduced length of ICU stay and length of hospital stay, and a reduction of hospital costs without an increase in readmission rate or a decrease in patient satisfaction (5,6,20).…”
Section: Improvement In Perioperative Carementioning
confidence: 99%
See 1 more Smart Citation